A Mixed Methods Evaluation of a Pilot Resilience Training Course on Stress Management - Shawn T. Mason; Chun Wang; Helen M.P. Scott; Jenn Lea; Jennifer Turgiss (Public Health, 2025)
Background: Chronic stress adversely affects biologic, cognitive and emotional functioning, is associated with worsened morbidity and mortality outcomes, and is predictive of performance and productivity. Interventions for resilience to stress can be effective but are typically time intensive. With contemporary life demands, effective, brief interventions may be advantageous.Methods: This single arm, mixed methods study evaluated the effectiveness of a 1-day resilience to stress training course. Thirty community participants were surveyed at baseline and 1-month. Qualitative interviews were conducted between 30-68 days post-intervention according to a grounded theory approach. Quantitative measures included Perceived Stress Scale (PSS), Public Health Surveillance Wellbeing (PHS-WB), Rand Medical Outcome Survey (MOS) SF-36, Health, and Productivity Questionnaire (HPQ), Work Productivity and Activity Impairment (WPAI) and Brief Cope Scale (BCS). Participants had a mean age of 53-years (SD=9) and were largely female (57%), caucasian (79%), married (83%), and employed (80%). Generalized estimating equations and paired sample t-tests were used to analyze quantitative data.Results: Participants self-reported improvement at 1-month on the PSS (moderate or high 100% vs. 50%, p<0.001), PHS-WB (29.8 vs. 31.5, p=.04), SF-36 subscales role limitation due to physical health (44.1 vs. 69.0, p=.002), vitality (55.2 vs. 63.6, p=.008), emotional wellbeing (70.9 vs. 78.0, p=0.001), and social functioning (76.0 vs. 87.9, p=0.003). Qualitative analysis suggested participants used the course as an opportunity to build a framework for action. Critical ideas triggered a recalibration of perspectives and reference points (i.e., mindsets) opening the way to updating routinized decisions and harnessing new ways of behaving in service of resilience. Embedding changes in behavior were swift for some or a gradual process of pragmatic adaption for others. Conclusions: Our pilot findings suggest that brief one-day interventions may facilitate personal reform and may enhance resilience and psychological wellbeing. Longer follows-ups to determine sustainability are also required.